The Impact of ESG Performance on Corporate Value: An Empirical Analysis Based on A-share Listed Companies - Huang, Jiaxin; Zhou, Zejiong (International Journal of Global Economics and Management, 2024)
With the deepening discussion of environmental, social, and governance issues on a global scale, enterprises, as an important part of the social economy, have attracted increasing attention to their own ESG performance. This article is based on data from Chinese A-share listed companies from 2013 to 2023. Through a fixed effects model, empirical research has found that the ESG performance of a company has a significant positive impact on its value, that is, as the ESG performance of a company improves, its value also increases. Enterprises can enhance their competitiveness by improving their ESG performance, gain recognition from more investors and stakeholders, and achieve sustainable development goals.